Hyperacute graft-versus-host disease of the skin following allogeneic stem cell transplantation: A paediatric case series - Gauri D Mahabal; Leni George; Dincy Peter; Meera Thomas; Biju George; Vikram Mathews; Aby Abraham; Alok Srivastava; Susanne Pulimood (Wolters Kluwer Medknow Publications, 2023)
Hyperacute GVHD (HaGVHD) is a rare complication of hematopoietic stem cell transplantation (HSCT) occurring before engraftment, a syndrome commonly involving skin and/or gut and/or liver, with increased morbidity and mortality. Myeloablative conditioning (MAC) regimes and mismatched donor transplants have an increased risk for HaGVHD. There is a higher chance of steroid-refractoriness and chronic GVHD in those who develop HaGVHD. There is limited literature about HaGVHD, especially in the paediatric age group. This retrospective single-centre case series included five paediatric patients who underwent HSCT between 1st April 2013 and 31st July 2015 at a tertiary care centre in South India, who fulfilled the criteria for HaGVHD as per criteria by Kim et al. and whose follow up data was available. We noted their risk factors, clinical course and prognosis. There were five paediatric HaGVHD patients. The risk factors noted among them were MAC regimen in three and mismatched unrelated donor sources in three. Two had steroid-refractory disease, four went on to develop chronic GVHD and three died of GVHD or treatment-related complications. A high index of suspicion is necessary to recognize HaGVHD, especially in patients with known risk factors developing a fever with rash post-HSCT.